Factors associated with reasons for men not seeking Primary Health Care services - Oliveira Barbosa, Yuri; Lima Menezes, Leonardo Philipe; de Jesus Santos, José Marcos; Oliveira da Cunha, Jéssica; Paz Albuquerque, Tales Iuri; da Conceição Araújo, Damião; Dantas dos Santos, Allan (O Mundo da Saúde, 2019)
For men to adhere to health services and to perceive themselves as the subject of their care, it is of utmost importance that professionals receive them through qualified listening, listening to their desires and difficulties giving them a welcoming environment. Given this, the objective of this study was to analyze the factors associated with the reasons why men do not seek Primary Health Care services. This was an exploratory, cross-sectional approach, quantitative approach, descriptive study with an analytical character. Data collection was performed through semi-structured interviews with the aid of the primary care assessment instrument in the adult version (PCATool-brasil adult version) with 485 adult men living in rural and urban areas of a city of Sergipe. Statistical analysis was performed using univariate and bivariate techniques, Fisher’s Chi-squared and Exact test by IBM® SPSS - Statistical Package for Social Sciences, version 20.0. There was an association with the delay in care reported by 173 (35.7%) respondents, which were among the rural residents and those with less education. Also, the absence of diseases reported by 164 men (33.8%) was associated with housing in rural areas; and the lack of reception by health professionals (16.7%; n=81) was higher among alcoholics and lower among rural residents. It is concluded that the reasons men do not seek the services offered in Primary Health Care are significantly interfered with by sociodemographic and lifestyle characteristics.